2011
DOI: 10.1111/j.1528-1167.2011.03003.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and autonomic cardiac function in patients with Dravet syndrome

Abstract: Summary Dravet syndrome (DS) is an epileptic encephalopathy related mainly to mutations in the SCN1A gene, encoding for neuronal sodium channels. Patients with DS have a high risk of sudden unexpected death in epilepsy (SUDEP). In this study we investigated whether patients with DS present abnormalities in electrical and autonomic cardiac function. To this aim we assessed ventricular repolarization and heart rate variability (HRV) on standard electrocardiography (ECG) and on 24‐h ECG Holter monitoring, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 15 publications
3
58
0
1
Order By: Relevance
“…In addition, they observed an increased number of atrioventricular blocks and decreased interictal heart rate variability in mice with global or brain-specific Na v 1.1 deletion. Consistent with this, children with Dravet syndrome exhibit decreased heart rate variability compared to age-and sex-matched children with other epilepsy syndromes or with healthy controls (10). This suggests that there may be abnormal regulation of sinoatrial node activity by the autonomic nervous system.…”
Section: Sudden Unexpected Death In Dravet Syndromesupporting
confidence: 66%
“…In addition, they observed an increased number of atrioventricular blocks and decreased interictal heart rate variability in mice with global or brain-specific Na v 1.1 deletion. Consistent with this, children with Dravet syndrome exhibit decreased heart rate variability compared to age-and sex-matched children with other epilepsy syndromes or with healthy controls (10). This suggests that there may be abnormal regulation of sinoatrial node activity by the autonomic nervous system.…”
Section: Sudden Unexpected Death In Dravet Syndromesupporting
confidence: 66%
“…For example, mutations of SCN1A in patients with DS cause increased QT and P wave dispersion and a decrease in heart rate variability (HRV) (12,37). However, there are no published reports of ECG changes after fatal or nonfatal generalized seizures in patients with DS, other than a single case report after status epilepticus (38).…”
Section: Introductionmentioning
confidence: 91%
“…A variety of mechanisms have been proposed for SUDEP (1,2,(4)(5)(6), including cardiac arrhythmias (7)(8)(9)(10), dysfunction of autonomic control (11)(12)(13)(14)(15), apnea/hypoventilation (3,(16)(17)(18)(19)(20)(21), airway obstruction (22), pulmonary edema (23), brain stem spreading depolarization (BSD) (24), and postictal generalized EEG suppression (PGES) (25). Many investigators have focused on cardiac tachyarrhythmias as the cause of death, in part because of an association between SUDEP and mutations of genes expressed in the heart, such as those that underlie long QT syndrome (10,(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Several other aspects of our studies of DS mice also correlate with observations of DS patients. Notably, as in DS mice, Delogu and colleagues (47) found that DS patients have suppressed resting heart-rate variability compared with other epileptic patients or nonepileptic individuals. Similarly, as in DS mice, most SUDEP cases in patients with DS and other types of epilepsy occur in sleep (9,12,47,48).…”
Section: Figurementioning
confidence: 99%